Documentation from trained medical students has a low rate of relative downcoding for emergency medicine encounters. Issue 3 (14th June 2022) - Tillman, David S.; Jewell, Corlin M.; Hekman, Dann J.; Nicholson, Adam M.; Schnapp, Benjamin H.; Lasarev, Michael R.; Alexandridis, Roxana; Hess, Jamie M.; Westergaard, Mary C.
Abstract: Background: Since 2018, the Centers for Medicare & Medicaid Services (CMS) guidelines have allowed teaching physicians to bill for evaluation and management services based on medical student documentation. Limited previous data suggest that medical student documentation suffers from a high rate of downcoding relative to faculty documentation. We sought to compare the coding outcomes of documentation performed by medical students, and not edited by faculty, with documentation edited and submitted by faculty. Methods: A total of 104 randomly selected notes from real patient encounters written by senior medical students were compared to the revised notes submitted by faculty. The note pairs were then split and reviewed by blinded professional coders and assigned level of service (LoS) codes 1–5 (corresponding to E&M CPT codes 99281–99285). Results: We found that the LoS agreement between student and faculty note versions was 63%, with 23% of all student notes receiving lower LoS compared to faculty notes (downcoded). This was found to be similar to baseline variability in professional coder LoS designations. Conclusions: Notes from medical students who have completed a focused documentation curriculum have less LoS downcoding than in previous reports.